2008
DOI: 10.21236/ada493820
|View full text |Cite
|
Sign up to set email alerts
|

Model P Wave Multipathing at Regional Distances in Southeast Asia

Abstract: Public reporting burden for this collection of information is estimated to average 1 hour per response, including the time for reviewing instructions, searching existing data sources, gathering and maintaining the data needed, and completing and reviewing this collection of information. Send comments regarding this burden estimate or any other aspect of this collection of information, including suggestions for reducing this burden to Department of Defense, Washington Headquarters Services, Directorate for Info… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2009
2009
2009
2009

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 33 publications
0
2
0
Order By: Relevance
“…Many previous studies have used seismic arrays to study regional-distance P-coda and in particular to detect later arriving phases associated with upper mantle triplications (Niazi and Anderson, 1965;Johnson, 1967;Simpson et al, 1974;King and Calcagnile, 1976;England et al, 1977;Ram and Mereu, 1977;England et al, 1978;Ram et al, 1978). A comprehensive review of these and related studies is given in Koper and Fatehi (2008). Here we briefly describe wave propagation in the transition zone to determine at what distances and with what properties triplicated phases are most likely to be observed in short-period P-coda.…”
Section: Overview Of P-wave Propagation At Regional Distancesmentioning
confidence: 99%
“…Many previous studies have used seismic arrays to study regional-distance P-coda and in particular to detect later arriving phases associated with upper mantle triplications (Niazi and Anderson, 1965;Johnson, 1967;Simpson et al, 1974;King and Calcagnile, 1976;England et al, 1977;Ram and Mereu, 1977;England et al, 1978;Ram et al, 1978). A comprehensive review of these and related studies is given in Koper and Fatehi (2008). Here we briefly describe wave propagation in the transition zone to determine at what distances and with what properties triplicated phases are most likely to be observed in short-period P-coda.…”
Section: Overview Of P-wave Propagation At Regional Distancesmentioning
confidence: 99%
“…There is a need for calibration at the International Monitoring System array CMAR (Chiang Mai, Thailand). First mentioned by Koch and Kraundofer (1997) and Bondar et al (1999), then by Guilbert et al (2005) and Koper and Fatehi (2008), significant effort was devoted to study-specific, empirical corrections of bias in back-azimuth observed at CMAR. However, even though dipping Mohorovičić discontinuity beneath CMAR was mentioned by Bondar et al, 1999 as a possible explanation of the observed parameter residuals, no further research was devoted to solving this hypothesis.…”
Section: Introductionmentioning
confidence: 99%